2016
DOI: 10.4172/2155-9570.1000530
|View full text |Cite
|
Sign up to set email alerts
|

Changes in BDNF and MAPK Signaling Pathways in Experimental Glaucoma

Abstract: Glaucoma is currently recognized to be a multifactorial, progressive, neurodegenerative disorder. It is characterized by the retinal ganglion cells (RGCs) loss of axons as well as optic nerve atrophy, progressive degeneration of RGCs till cell death. In this work, we used DBA/2J mice as a model of spontaneous glaucoma and we investigated the involvement of BDNF and Mitogen-Activated Protein Kinases (MAPK) pathways in correlation with IOP elevation and progression of neurodegenerative processes in the retina of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…The functional activity of BDNF is manifested through its interaction with the TrkB receptor, leading to the activation of intracellular signaling pathways associated with cell viability, including the phosphatidylinositol-3 kinase (PI-3 K)/Akt and extracellular signal-regulated kinases 1/2 (Erk1/2) pathways. Both of these signaling pathways have been implicated in experimental glaucoma ( Cheng et al, 2002 ; Carlotta et al, 2016 ; Liang et al, 2019 ). There are several studies using different models of glaucoma that indicate that local administration of BDNF to the eye results in reduced loss of RGCs.…”
Section: Molecular Mechanisms Of Glaucoma Developmentmentioning
confidence: 99%
“…The functional activity of BDNF is manifested through its interaction with the TrkB receptor, leading to the activation of intracellular signaling pathways associated with cell viability, including the phosphatidylinositol-3 kinase (PI-3 K)/Akt and extracellular signal-regulated kinases 1/2 (Erk1/2) pathways. Both of these signaling pathways have been implicated in experimental glaucoma ( Cheng et al, 2002 ; Carlotta et al, 2016 ; Liang et al, 2019 ). There are several studies using different models of glaucoma that indicate that local administration of BDNF to the eye results in reduced loss of RGCs.…”
Section: Molecular Mechanisms Of Glaucoma Developmentmentioning
confidence: 99%
“…TrkB is also highly expressed in the RGC dendrites and cell bodies [79]. Although the primary source of BDNF supply for RGCs is known to be the brain, studies have also demonstrated that there is a level of local expression of this neurotrophin in the RGCs, Müller glial cells, and astrocytes [80]. Following BDNF binding, TrkB is activated through dimerization and autophosphorylation on its critical intracellular tyrosine residues [61].…”
Section: Bdnf/trkb Signalingmentioning
confidence: 99%
“…Several models of glaucoma have indicated that inflammatory components can directly link elevated IOP with retinal degeneration . As a result, the expression of inflammatory molecules, including nitric oxide, interleukins (ILs), p38 MAPK, and prostaglandin E2 (PGE2), are increased in progressive glaucoma. Furthermore, inflammatory progression is also associated with the increased expression of matrix metalloproteinases (MMPs), which consequently induce the degradations of extracellular matrix (ECM) components such as stromal collagen and retinal laminin .…”
Section: Introductionmentioning
confidence: 99%